The effect of red dragon fruit (Hylocereus polyrhizus) peel meal on internal organs, ileal coliform, and growth performances in broiler chickens - Iis Yuanita; Lisnawaty Silitonga; Hanna Oktaviani Br. Ginting; Elysabet Christiani; Lisna Lisna; Rizky Fajar; Efraim Tobias (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The study evaluated the effect of feeding red dragon fruit (Hylocereus polyrhizus) peel meal on internal organs, ileal coliform counts, and growth performances in broiler chicken. A total of 96 birds of unsexed one-day-old broiler (Ross strain) were randomly divided into four dietary treatments and six replications with four birds each. The dietary treatments were basal diet as a control diet (DPM0), basal diet added with 0.5% red dragon fruit peel meal (DPM1), and 1% red dragon fruit peel meal (DPM2), and 1.5% red dragon fruit peel meal (DPM3). The cecum and carcass percentage in the broiler was significantly enhanced (p<0.05). At the same time, the coliform total in the ileum and abdominal fat were significantly decreased (p<0.05) with the increasing level of feeding dragon fruit peel meal. The difference in other internal organs' feed intake and body weight gain during the treatments were insignificant (p>0.05) after five weeks of feeding. In conclusion, the red dragon fruit peel meal effectively improves growth performance and gut health by increasing carcass percentage and decreasing abdominal fat production and ileal coliform count in broiler chickens.